Analisis Kinerja Petugas Airport Operation Landside Dan Terminal (Aolt) Dalam Menunjang Kegiatan Inspeksi Fasilitas Di Bandar Udara Internasional Adisutjipto Yogyakarta - Ridho Fahrul Rozi Permana; Yunus Purnama (STIKes Ibnu Sina Ajibarang, 2024)
Airport Operation Landside and Terminal (Aolt) officers still often find field inspections and find findings stating that the facilities in the airport terminal area are functioning normally, the facilities are normal and the toilets are clean and fragrant and dry, all findings are documented to be reported and repairs are carried out by the relevant units to carry out checks and all activities and findings regarding damage to facilities are reported in the manual log book recording and the my inspection application. This researcher aims 1). Knowing the performance of AOLT officers at Adisutjipto Yogyakarta International Airport.2). Find out what the role of officers is in inspecting facilities at the Yogyakarta Adisutjipto International Airport terminal. 3). Knowing the efforts of AOLT officers in overcoming obstacles to inspection of facilities at Adisutjipto International Airport. This research uses qualitative methods. Research subjects and objects, researchers are supported by data collectors using observation methods, interview methods, and documentation methods with supporting documents at the Airport Operation Landside and Terminal (Aolt) units to answer the research problem formulation, the researchers carried out 3 stages of data analysis techniques consisting of data reduction, data presentation, and conclusions and verification. The results of this research show that 1) AOLT officers have compliance with good inspection procedures, adequate abilities in identifying problems, and effective reporting and communication processes, 2) Airport Operation Lanside and Terminal officers at Adisutjipto Yogyakarta International Airport have a major role in monitoring facility conditions, reporting findings, corrective actions, and coordinating with related parties. 3) In handling facilities, the solutions implemented must focus on expanding facilities, regular maintenance, improving services, and collaborating with related parties. In this way, airport toilets can become more comfortable facilities and meet higher standards.